Gestational syphilis: a socioeconomic analysis of the increase in rates in Brazil (International Seven Journal of Multidisciplinary, 2024)
Syphilis is a sexually transmitted infection (STI) that has been known since the 15th century. This pathology, whose etiological agent is Treponema Pallidum, can be classified as: acquired, gestational or congenital, since transmission can be sexual or vertical, from mother to fetus. In recent years, gestational syphilis has seen a progressive and considerable increase in the number of cases detected in Brazil. Thus, knowing that this disease puts not only the pregnant woman's life at risk, but also that of the fetus, which can acquire the infection via transplacental transmission, it is extremely important to understand the factors involved in the increase in the number of detected cases of gestational syphilis, which is the main objective of this research. From a socio-economic perspective, the article discusses the correlation between the increase in cases and social inequality factors in areas of Brazil, understanding how the particularities of each region are reflected in health management, based on the incidence of the disease. As a methodology, we plan to carry out a bibliographical review based on books and catalogued scientific articles published in online indexed databases, such as Scientific Library Online (SciElo) and Pubmed. In addition, an analysis of data from the DATASUS platform will be carried out, also from the 2010 Census. As expected results, we believe that the increase in the rate of gestational syphilis is closely related to socioeconomic factors and access to adequate prenatal care.